ANALISIS PENGETAHUAN E-MONEY TERHADAP MINAT PENGGUNAAN UANG ELEKTRONIK PADA MAHASISWA SEKOLAH TINGGIILMU EKONOMI ENAM ENAM KENDARI - Luna Noviantheza Rosari; Muh. Nur; Arifin (STIE ENAM ENAM KENDARI, 2022)
The purpose of the study was to identify and analyze and determine the effect of E-Money on the interest in using electronic money in the Sekolah Tinggi Ilmu Ekonomi Enam-Enam Kendari. The population in this study were students of the Sekolah Tinggi Ilmu Ekonomi Enam-Enam Kendari who were still actively studying, consisting of the 2018 class and the 2019 class, which totaled 901 students. The sample in this study was some students of the Sekolah Tinggi Ilmu Ekonomi Enam-Enam Kendari who are still actively studying, consisting of the 2018 and 2019 batches, totaling 90 students using the Slovin method. The data analysis method used is quantitative descriptive analysis. The analytical tool used is simple Linear Regression. The results of the study state that knowledge of E-Money has a positive and significant effect on interest in using electronic money in students of the Sekolah Tinggi Ilmu Ekonomi Enam-Enam Kendari, meaning that the higher the knowledge of E-Money students, the interest in using it will also increase.